Food Aid Sharing and Resilience. The role of collectivity and connectivity in drought-affected pastoralist systems in Ethiopia - Flintan, Fiona E.; Anbacha, Abiyot; Ebro, Abule; Eba, Bedasa; Disasa, H.; Aden, H.; Abdulatif, M.; Assefa, A. (Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises, 2025)
A brief summarizing a study undertaken in three specifically selected kebeles of Su’ula (in Afar region), Asli (Somali), and Fuldowa (Oromia) that had received food aid during the drought of 2020–2023. The resilience of pastoralist communities in Ethiopia during drought relies heavily on their connectivity and collective efforts. Humanitarian strategies that embrace these dynamics can significantly enhance coping mechanisms and sustainability. Policymakers must prioritize reinforcing community networks to ensure effective humanitarian responses that are culturally sensitive and community centered.